Effects of different training intensity distributions between elite cross-country skiers and nordic-combined athletes during live high-train low - Schmitt, L.; Willis, S. J.; Coulmy, N.; Millet, G. P. (Frontiers in Physiology, 2018)
Purpose: To analyze the effects of different training strategies (i.e., mainly intensity distribution) during living high - training low (LHTL) between elite cross-country skiers and Nordic-combined athletes. Methods: 12 cross-country skiers (XC) (7 men, 5 women), and 8 male Nordic combined (NC) of the French national teams were monitored during 15 days of LHTL. The distribution of training at low-intensity (LIT), below the first ventilatory threshold (VT1), was 80% and 55% in XC and NC respectively. Daily, they filled a questionnaire of fatigue, and performed a heart rate variability (HRV) test. Prior (Pre) and immediately after (Post), athletes performed a treadmill incremental running test for determination of V.O2max and V.O2 at the second ventilatory threshold ( V.O2V T2), a field roller-skiing test with blood lactate ([La-]) assessment. Results: The training volume was in XC and NC, respectively: at LIT: 45.9 ± 6.4 vs. 23.9 ± 2.8 h (p < 0.001), at moderate intensity: 1.9 ± 0.5 vs. 3.0 ± 0.4 h, (p < 0.001), at high intensity: 1.2 ± 0.9 vs. 1.4 ± 02 h (p = 0.05), in strength (and jump in NC): 7.1 ± 1.5 vs. 18.4 ± 2.7 h, (p < 0.001). Field roller-skiing performance was improved (-2.9 ± 1.6%, p < 0.001) in XC but decreased (4.1 ± 2.6%, p < 0.01) in NC. [La-] was unchanged (-4.1 ± 14.2%, p = 0.3) in XC but decreased (-27.0 ± 11.1%, p < 0.001) in NC. Changes in field roller-skiing performance and in [La-] were correlated (r = -0.77, p < 0.001). V.O2max increased in both XC and NC (3.7 ± 4.2%, p = 0.01 vs. 3.7 ± 2.2%, p = 0.002) but V.O2V T2 increased only in XC (7.3 ± 5.8%, p = 0.002). HRV analysis showed differences between XC and NC mainly in high spectral frequency in the supine position (HFSU). All NC skiers showed some signs of overreaching at Post. Conclusion: During LHTL, despite a higher training volume, XC improved specific performance and aerobic capacities, while NC did not. All NC skiers showed fatigue states. These findings suggest that a large amount of LIT with a moderate volume of strength and speed training is required during LHTL in endurance athletes.